Non-surgical Treatments for Lung Metastases in Patients with Soft Tissue Sarcoma: Stereotactic Body Radiation Therapy (SBRT) and Radiofrequency Ablation (RFA) - Tetta, Cecilia; Carpenzano, Maria; Algargoush, Areej T.J.; Algargoosh, Marwah; Londero, Francesco; Maessen, Jos G.; Gelsomino, Sandro (Current Medical Imaging, 2021)
Background: Radio-frequency ablation (RFA) and Stereotactic Body Radiation Therapy (SBRT) are two emerging therapies for lung metastases. Introduction: Aliterature review was performed to evaluate the outcomes and complications of these procedures in patients with lung metastases from soft tissue sarcoma (STS). Methods: After selection, seven studies were included for each treatment encompassing a total of 424 patients: 218 in the SBRT group and 206 in the RFA group. Results: The mean age ranged from 47.9 to 64 years in the SBRT group and from 48 to 62.7 years in the RFA group. The most common histologic subtype was, in both groups, leiomyosarcoma. In the SBRT group, median overall survival ranged from 25.2 to 69 months and median disease- free interval was from 8.4 to 45 months. Two out of seven studies reported G3 and one G3 toxicity, respectively. In RFA patients, overall survival ranged from 15 to 50 months. The most frequent complication was pneumothorax. Local control showed a high percentage for both procedures. Conclusion: SBRT is recommended in patients unsuitable to surgery, in synchronous bilateral pulmonary metastases, in case of deep lesions and patients receiving high-risk systemic therapies. RFA is indicated in case of a long disease-free interval, in oligometastatic disease, when only the lung is involved, in small size lesions far from large vessels. Further large randomized studies are necessary to establish whether these treatments may also represent a reliable alternative to surgery.
Keywords: Soft tissue sarcoma